IITA/BAYER modern breeding Project - virtual launch - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
Launching of the IITA/Bayer partnership for Modern Breeding Project funded by the Bill & Melinda Gates foundation and through the generous support from Bayer on 22 July 2020.